AI in Fatwā Issuance: A SWOT Analysis of Opportunities and Limitations - Edy Saputra; Ahmad Afandi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2025)
The rapid development of artificial intelligence (AI) has opened new possibilities in various aspects of Islamic religious practice, including fatwā issuance processes. While AI demonstrates significant potential in enhancing the efficiency and accessibility of Islamic legal opinions, fundamental questions remain regarding its appropriate role and limitations within traditional ijtihād frameworks. This study examines the potential and boundaries of AI as a supporting instrument in fatwā processes through a comprehensive SWOT analysis and case study evaluation. Employing qualitative literature review methodology combined with content analysis of AI implementations at Dar al-Ifta Miṣr and automated fatwā generation systems, this research identifies AI's capabilities and constraints in Islamic jurisprudential contexts. Findings reveal that AI can enhance efficiency by up to 70% in administrative stages, particularly in evidence searching, madhhab opinion mapping, and comparative analysis of contemporary fatwās. AI's strengths include big data processing capacity, 24/7 accessibility, and cross-madhhab analytical capabilities. However, critical limitations exist in understanding psychological dimensions of mustaftīs, comprehending maqāṣid al-sharīʿah holistically, and performing creative ijtihād for novel cases. The SWOT analysis further identifies external threats, including potential replacement of muftī authority, commercialization risks, and fiqh homogenization. This study concludes that AI should be positioned as a non-binding decision-support system within a human-in-the-loop model, where final substantive fatwā authority remains exclusively with qualified human muftīs. Nine operational recommendations are provided for fatwā institutions, AI developers, educational institutions, and government regulators to ensure responsible and proportional AI implementation aligned with Islamic epistemological and ethical values.